Whole-genome deep sequencing of A(H3) influenza virus detected among vaccinated and unvaccinated individuals during 2016/2017 season, Portugal - Pechirra, Pedro (2017)
Vaccination is the best way to prevent influenza. This study aims to analyse the whole genome of influenza viruses from vaccinated and unvaccinated cases and reveal possible viral genetic causes assigned to the vaccine failure. In the scope of the EuroEVA/I-MOVE project, nasopharyngeal swabs were collected from patients with influenza like illness selected in primary care settings. Viral RNA was extracted directly from biological samples and after multiplex PCR amplification, the whole genome was sequenced for 84 influenza A(H3) viruses by deep sequencing on a MiSeq platform. The influenza gene sequences were assembled using a in-house multi-software pipeline with a mean depth of coverage of 1144x. Multiple gene alignments and mutational analysis was performed on MEGA software 6.0. All A (H3) virus clustered in the 2 genetic groups 3C.2a and 3C.2a1 (predominant). Sixteen viruses (19%) were from vaccinated individuals (10% in 3C.2a and 25% in 3C.2a1 groups). Only 7 cases of vaccine failure presented amino acid substitutions, not found among unvaccinated cases. No difference was found between vaccinated and unvaccinated groups in the p-distance, number of synonymous and nonsynonymous substitutions of viral genes. Only 5 cases of vaccine failure harbored nucleotide variants on their genome (from 7 detected sequence variants, only one has changed the amino acid). The proportion of vaccinated cases was higher in new 3C.2a1 group than in 3C.2a. Few amino acid substitutions found only in vaccinated cases occurred sporadically, as well as the nucleotide variants, most of them are synonymous substitutions. We found no differences in the type of selection, driving the viruses detected in vaccinated and unvaccinated cases.